EP954 Impact of Splenectomy on survival in advanced ovarian cancer (AOC) in a propensity matched cohort. (1st November 2019) - Davies, J; Asher, V; Bali, A; Abdul, S; Gomez, D; Tou, S; Persic, M; Seneviratne, L; Phillips, A
Abstract : Introduction/Background: Ultra-radical procedures, including splenectomy, are utilised during cytoreductive surgery in AOC to treat disease that would not be removed with standard procedures, the intention being to increase complete cytoreduction rates. Hypothetically the performance of splenectomy may independently be a marker for worse survival due to detrimental effects on immune function or its complications. Methodology: A retrospective review of all consecutive patients undergoing cytoreductive surgery for AOC between 16/05/2013–6/02/2019. Survival, complications and surgical parameters were recorded. Propensity scored matching (PSM) was performed, allowing comparison between splenectomy patients with both standard and ultra-radical surgery without splenectomy. Results: 151 patients were identified within a 71 month time period. Of these 100 underwent standard and 51 underwent ultra-radical surgery. 22 patients received splenectomy (14.5%) No difference was seen in Overall survival (OS) between all patients (median OS 34 months (95% CI 25.9–41.1) and patients undergoing splenectomy (median OS not yet reached) (p≥0.05). When comparing UR only patients, neither arm reached median OS; HR=1.8 (0.64–5.3), p>0.05. After PSM for grade, stage, age and cytoreduction, no significant difference in splenectomy versus non-splenectomy patients (3-year survival 54% compared to 56% (hazard ratio - 1.1 (95% CI 0.39–3.2). (P>0.05). When matching only to Ultra radical controls, no significant difference in OS was seen with median OS not reached in either arm (HR - 2.6(0.55–13) p>0.05). Splenectomy specific complications were seen in 3 patients; one pancreatic tail injury, one left pleural effusion and one cases of streptococcal pharyngitis during chemotherapy. No cases of overwhelming post splenectomy infection were identified. Conclusion: Splenectomy does not negatively impact the complication rates of surgery or survival; and should not be feared by gynaecological oncologist undertaking ultra-radical surgery for AOC. Disclosure: Nothing to disclose.